Sudden Infant Death Syndrome – Role of Trigeminocardiac Reflex: A Review - Singh, Gyaninder Pal; Chowdhury, Tumul; Bindu, Barkha; Schaller, Bernhard (Frontiers in Neurology, 2016)
Sudden infant death syndrome (SIDS) is an unexplained death in infants that usually occurs during sleep. The cause of SIDS remains unknown and multifactorial. In this regard, the diving reflex (DR), a peripheral subtype of trigeminocardiac reflex (TCR) is also hypothesized as one of the possible mechanisms for this condition. The TCR is a well-established neurogenic reflex which manifests as bradycardia, hypotension, apnea, and gastric hyper motility. The TCR shares many similarities with the DR which is a significant physiological adaptation to withstand hypoxia during apnea in many animal species including humans in clinical manifestation and mechanism of action. The DR is characterized by breath-holding (apnea), bradycardia and vasoconstriction leading to rising in blood pressure. Several studies have described congenital anomalies of autonomic nervous system in the pathogenesis of SIDS such as hypoplasia, delayed neuronal maturation or decreased neuronal density of arcuate nucleus, hypoplasia and neuronal immaturity of the hypoglossal nucleus. The abnormalities of autonomic nervous system in SIDS may explain the role of TCR in this syndrome involving sympathetic and parasympathetic nervous system. We reviewed the available literature to identify the role of TCR in the etiopathogenesis of SIDS and the pathways and cellular mechanism involved in it. This synthesis will help to update our knowledge and improve our understanding about this mysterious, yet common condition and will open the door for further research in this field.